Prescription Medications and Co-Morbidities in Late Middle-Age are Associated with Greater Cognitive Declines: Results from WRAP - Du, Lianlian; Koscik, Rebecca Langhough; Chin, Nathaniel A.; Bratzke, Lisa C.; Cody, Karly; Erickson, Claire M.; Jonaitis, Erin; Mueller, Kimberly D.; Hermann, Bruce P.; Johnson, Sterling C. (Frontiers in Aging, 2022)
The present study investigated: 1) sex differences in polypharmacy, comorbidities, self-rated current health (SRH), and cognitive performance, 2) associations between comorbidities, polypharmacy, SRH, and objective measures of health, and 3) associations of these factors with longitudinal cognitive performance. Analyses included 1039 eligible Wisconsin Registry for Alzheimer’s Prevention (WRAP) participants who were cognitively unimpaired at baseline and had ≥2 visits with cognitive composites, self-reported health history, and concurrent medication records. Repeated measures correlation (rmcorr) examined the associations between medications, co-morbidities, SRH, and objective measures of health (including LIfestyle for BRAin Health Index (LIBRA), and depression). Linear mixed-effect models examined associations between medications, co-morbidities, and cognitive change over time using a preclinical Alzheimer’s cognitive composite (PACC3) and cognitive domain z-scores (executive function, working memory, immediate learning, and delayed recall). In secondary analyses, we also examined whether the number of medications interacted with co-morbidities and whether they modified age-related cognitive trajectories. The number of prescribed medications was associated with worse SRH and a higher number of self-reported co-morbidities. More prescribed medications were associated with a faster decline in executive function, and more comorbidities were associated with faster PACC3 decline. Those with a non-elevated number of co-morbidities and medications performed an average of 0.26 SD higher (better) in executive function and an average of 0.18 SD higher on PACC3 than those elevated on both. Associations between medications, co-morbidities, and executive function, and PACC3 suggest that persons with more co-morbidities and medications may be at increased risk of reaching clinical levels of impairment earlier than healthier, less medicated peers.